Drosophila p53 isoforms have overlapping and distinct functions in germline genome integrity and oocyte quality control. - Chakravarti, A.; Thirimanne, H.N.; Brown, S.; Calvi, B.R. (eLife, 2022)
p53 gene family members in humans and other organisms encode a large number of protein isoforms whose functions are largely undefined. Using Drosophila as a model, we find that a p53B isoform is expressed predominantly in the germline where it colocalizes with p53A into subnuclear bodies. It is only p53A, however, that mediates the apoptotic response to ionizing radiation in the germline and soma. In contrast, p53A and p53B are both required for the normal repair of meiotic DNA breaks, an activity that is more crucial when meiotic recombination is defective. We find that in oocytes with persistent DNA breaks p53A is also required to activate a meiotic pachytene checkpoint. Our findings indicate that Drosophila p53 isoforms have DNA lesion and cell type-specific functions, with parallels to the functions of mammalian p53 family members in the genotoxic stress response and oocyte quality control.